Evaluating impact of Soil Conservation Service curve number-dependent and independent excess-rainfall computing approaches on total runoff volumes and peak run- off rates simulated through a Geomorphic Instantaneous Unit Hydrograph model - Ravinder Kaur; Saleh Arekhi (Journal of Soil and Water Conservation, 2022)
The effect of SCS curve number dependent (CNhandbookM4 CN derived d1i.e. conventional) and curve number independent (i.e. CN_independent i.e., proposed) excess-rainfall computing approaches on the accuracy of total runoff volumes and peak run-off rates estimated through a geomorphic instantaneous unit hydrograph (GIUH) model was investigated. The above three approaches were tested on 16 test storms for a micro-watershed (0.40 km2) in Almora district of Uttaranchal. It was observed that use of a SCS-CNhandbook method, for accounting rainfall abstractions in the GIUH model, resulted into highly under-estimated total runoff volumes (mean relative error i.e. MRE= -47%) and peak runoff rates (MRE: -21%). In contrast to this, accounting of rainfall abstractions though the SCS-CN_independent and SCS-CNderived methods in the GIUH model resulted into estimated total runoff volumes and peak runoff rates with only 1 to 15% mean relative errors. The present investigation could thus clearly show that initial and maximum potential retentions, in the GIUH model, could be very realistically accounted by both SCS-CN_independent and SCS-CN derived methods. It was hence suggested that, depending upon input data availability, the two methods are interchangeable. However, as compared to the SCS-CN derived method, the proposed SCS-CN_independent method was observed to be requiring no accounting of rarely monitored storm based discharge data and antecedent moisture conditions. Hence its successful replacement for SCS-CNderived excess-rainfall simulating method was even suggested to increase the scope of such GIUH technique based runoff models to be applied on ungauged/ in-adequately gauged watersheds.